2022
DOI: 10.5056/jnm21254
|View full text |Cite
|
Sign up to set email alerts
|

Subtype of Achalasia and Integrated Relaxation Pressure Measured Using the Starlet High-resolution Manometry System: A Multicenter Study in Japan

Abstract: Background/AimsManoScan and Sandhill high-resolution manometry (HRM) systems are used worldwide; however, the diagnosis of achalasia on the Starlet HRM system is not fully characterized. Furthermore, the impact of calcium channel blockers and nitrites in treating achalasia has not been investigated using HRM. Management of recurrent cases is a priority issue, although few studies have examined patient characteristics. MethodsWe conducted a multicenter, large-scale database analysis. First, the diagnosis of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
3
0
1
Order By: Relevance
“…Demographics are known to play a role in IRP. Similar to our findings, male gender and older age have been previously reported to be associated with lower IRP values in achalasia patients [ 13 , 14 ]. Surprisingly, our study found ethnicity to be even more significantly associated with IRP values.…”
Section: Discussionsupporting
confidence: 93%
“…Demographics are known to play a role in IRP. Similar to our findings, male gender and older age have been previously reported to be associated with lower IRP values in achalasia patients [ 13 , 14 ]. Surprisingly, our study found ethnicity to be even more significantly associated with IRP values.…”
Section: Discussionsupporting
confidence: 93%
“…We conducted a multicenter study involving 14 high-volume centers in Japan, namely, the Japan Achalasia Multicenter study (JAMS) and analyzed a large number of patients with EMDs. 10,13 Consecutive series of patients with EMDs diagnosed using standard methods, including HRM, esophagography, and esophagogastroscopy, from 2010 and 2020, were enrolled in the JAMS. All diagnoses were performed by experts with extensive experience in the diagnosis of EMDs.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the characteristics of patients in these disorders should be clarified to help differential diagnosis, and the cut-off values of the intraluminal pressure at EGJ should be established. In Starlet HRM, the frequency of type I achalasia diagnosis is relatively higher than that of type II, different from the Manoscan or Sandhill HRM systems 10 ; therefore, the opportunity to concern the differential diagnosis is considered much higher.…”
Section: Introductionmentioning
confidence: 99%
“…Pada penilitian Tetsuya Tatsuta, Dkk (2022) disimpulkan bahwa penghambat saluran kalsium dapat meringankan gejala, meskipun tidak dengan mengurangi nilai integrated relaxation pressure. Kasus akalsia yang berulang memiliki karakteristik pasien yang berbeda, dan strategi terbaik harus ditentukan berdasarkan hal ini (Tatsuta et al, 2022).…”
Section: Penelitian Terkaitunclassified